The association between tumor necrosis factor‐α‐308 G/A polymorphism and risk for vitiligo: a meta‐analysis. (29th July 2015) - Wu, Dongze; Shi, Deshun; Zhu, Xiaoliang
Abstract Background The contribution of tumor necrosis factor‐α (TNF‐α)‐308 G/A gene polymorphism (rs1800629) to risk for vitiligo is subject to controversy. Objectives The fundamental purpose of the present meta‐analysis was to investigate large‐scale evidence to determine the overall association between TNF‐α‐308 G/A polymorphism and susceptibility to vitiligo. Methods A literature search of the PubMed, EMBASE, Web of Science, and China National Knowledge Infrastructure (CNKI) databases was conducted to identify all studies referring to an association between TNF‐α‐308 G/A polymorphism and vitiligo published to June 1, 2014. The principal outcome measure for evaluating the strength of the association was the crude odds ratio (OR) along with the corresponding 95% confidence interval (CI). Data were extracted, and statistical analyses were implemented using stata Version 12.0. Results Data for a total of 1505 vitiligo cases and 2253 controls from five case–control studies concentrating on the association between TNF‐α‐308 G/A polymorphism and vitiligo were included in this meta‐analysis. Combined analysis revealed there to be no association between this polymorphism and susceptibility to vitiligo in five genetic models under random‐effects models. A subgroup analysis by clinical type also demonstrated the absence of any association between TNF‐α‐308 G/A polymorphism and generalized vitiligo. However, a significant association was detected in the miscellaneous subgroup under the dominant model (fixed‐effects model: OR 5.69, 95% CI 4.70–6.88; P = 0.000) and overdominant model (random‐effects model: OR 5.24, 95% CI 2.26–12.17; P = 0.000). Conclusions This meta‐analysis indicates that TNF‐α‐308 G/A polymorphism is not a genetic risk factor for vitiligo.